A STEM-BASED LEARNING PROCESS ANALYSIS OF STUDENTS' SCIENCE PROCESS SKILLS - Wiwit Artika; Andi Ulfa Tenri Pada; Safrida Safrida; Abdullah Abdullah; Nurrahmah Akbariah (Jurnal Penelitian Pendidikan IPA, 2023)
The STEM-based learning process spurs the creativity of students in knowledge, skills and others. Students' science process skills are very supportive in improving the quality of education to solve problems in everyday life. This study aims to determine the suitability of the learning process by pre-service teachers with the learning planning stages, students' science process skills and the correlation between the learning process and science process skills. This research is quantitative and qualitative through descriptive research. The results showed that the value of the results of observations on the learning process by the pre-service teacher was in the good category. The value of students' science process skills is in the sufficient category. There is a correlation between the STEM-based learning process and students' science process skills, which means that the STEM-based learning process affects students' science process skills even though it is small. The conclusion in this study is that the STEM-based learning process on science process skills has a positive relationship to the quality of student learning